2009
DOI: 10.3233/isu-2009-0592
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of computer based patient education resources to enable diabetic patients from underserved populations to self-manage their disease

Abstract: This pilot randomized prospective controlled pilot study looked at computer based health information resources and their impact on control of diabetes. The study site was a large urban community health center with many Spanish-speaking patients. Both the intervention (n = 58) and control (n = 50) groups of the study received standard of care diabetes treatment. The intervention group received additional computer based diabetes education in either English or Spanish from the Medline-Plus.gov website. Clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
1
2
Order By: Relevance
“…Finally, the system might have given patients a sense of reassurance or responsibility to remain healthy, thereby resulting in increased motivation to adhere to treatments and a healthy lifestyle. Our study and a number of others [24][25][26] found no significant benefits of CHITs over a control group for control of glycemia in patients with diabetes. However, previous reviews have reported that the use of CHITs was generally associated with a decline in the HbA1c level [5,8,9].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Finally, the system might have given patients a sense of reassurance or responsibility to remain healthy, thereby resulting in increased motivation to adhere to treatments and a healthy lifestyle. Our study and a number of others [24][25][26] found no significant benefits of CHITs over a control group for control of glycemia in patients with diabetes. However, previous reviews have reported that the use of CHITs was generally associated with a decline in the HbA1c level [5,8,9].…”
Section: Discussioncontrasting
confidence: 51%
“…However, previous reviews have reported that the use of CHITs was generally associated with a decline in the HbA1c level [5,8,9]. One possible explanation for the inconsistency may be that those empirical studies [24][25][26] (and this study) had a short study period to allow for possible changes in the HbA1c level. A recent metaanalysis showed that CHITs implemented over a longer period showed a more pronounced decrease in the HbA1c level than those with a short period (−0.33; 95 % CI, −0.50 to −0.17 for 12 months or more; −0.38; 95 % CI, −0.58 to −0.19 for 4 to 11 months; −0.23; 95 % CI, −0.38 to −0.08 for 3 months or less) [9].…”
Section: Discussioncontrasting
confidence: 51%
“…self-reported perceptions of poor health and functional capacity as measured by reliable, validated survey instruments) or objective such as glycated hemoglobin (A1C) (UKPDS Trial, 2002) and low-density lipoprotein cholesterol (Zyskind, Jones, Pomerantz, & Barker, 2009).…”
Section: Methodological Rigormentioning
confidence: 99%